Management of Anemia in Pregnant Women with Non-Pharmacological Methods: Literature Review - Nurdiana, Rossa Amelinda; Meiranny, Arum (Jurnal Maternitas Kebidanan, 2025)
Pregnancy is a physiological process in a woman. A pregnant woman willexperience changes in her body system during pregnancy. Pregnant women will besusceptible to anemia due to several things such as hemodilution and lack of ironintake. Anemia is included in a global problem which in Indonesia itself has arelatively high incidence rate, namely 48.9% in 2018, so an effective strategy isneeded to overcome this problem. The aim of this research is to determine the non-pharmacological management of anemia in pregnancy. The method used was aliterature review of 10 research articles contained in computerized databases(Google Scholar and Wiley) in the last 5 years using the keywords anemia, anemiamanagement, non-pharmacology and pregnancy. As a result, non-pharmacologicaltreatment of pregnancy with anemia can be done by consuming tomato herbal tea,chayote, mung bean juice, vegetable juice combined with various other ingredientssuch as spinach-lime-honey juice, dates, tempeh, and jackfruit seed milk, becausethe high vitamin C and iron contained in it make it a good source of nutrients toincrease hemoglobin production and maintain body health. The conclusion is,vitamin C and iron are an ideal combination of compounds to overcome anemia inpregnant women, because iron helps the production of hemoglobin and vitamin Cincrease iron absorption, thereby helping to overcome and prevent anemia andimprove the health of the mother and fetus